How paediatric departments in Sweden facilitate giving children a voice on their experiences of healthcare: A cross‐sectional study - Anna Nordlind; Ann‐Sofie Sundqvist; Agneta Anderzén‐Carlsson; Ann‐Charlotte Almblad; Karin Ängeby (Wiley, 2022)
Abstract Background In January 2020, the United Nations Convention on the Rights of the Child was incorporated into Swedish law. According to Swedish regulations, patients are to be given the opportunity to participate in quality improvement. Sometimes, the patients are children who have the right to be heard on matters concerning them, such as their experience of a hospital visit. Objective This study aimed to describe how Swedish paediatric departments facilitate children's voices on their healthcare experiences and how their perspectives are taken into account in quality improvement work. Methods This study has a descriptive cross‐sectional design. Data were collected using a study‐specific survey sent by e‐mail to all the heads of the paediatric departments in Sweden, with both inpatient and outpatient care. The response rate was 74% (28 of 38 departments). Results The results demonstrated a variation in questionnaires used and to whom they were targeted; less than half of the participating departments reported having had questionnaires aimed at children. The results also indicated a major variation in other working methods used to allow children to voice their experiences in Swedish paediatric departments. The results indicate that the national co‐ordination in facilitating the children's rights to be heard on their experiences in healthcare organisations can be improved. Conclusion Further research is required to ascertain which method is the most practically effective in paediatric departments, in what way children prefer to be heard regarding their experience of and perspectives on healthcare, and what questions need to be asked. A validated national patient‐reported experience measure developed with and aimed at children could provide them with equal opportunities to voice their experiences in healthcare, regardless of their diagnoses or which paediatric department they visit.